Pharmacy driven assessment of appropriate antibiotic selection in patients with reported beta‐lactam allergy. Issue 5 (7th June 2019) - Holmes, Ashley K.; Bennett, Nicholas T.; Berry, Timothy P.
Abstract: Background: Reported beta‐lactam (BL) antibiotic allergies lead to the avoidance of BL antibiotics. Despite that less than 10% of patients reporting have a true allergy, the documentation often leads to an increased use of alternative antibiotics. These nonpreferred antibiotics (NPA) have a significant impact on cost, clinical outcomes, and antimicrobial resistance. Objective: The primary objective of this study was to assess the impact of a pharmacy‐driven assessment on the prescribing frequency of penicillin or cephalosporin antibiotics in patients with a reported BL allergy. Methods: This retrospective cohort analysis evaluated the effect of a best practice alert (BPA) and subsequent allergy assessment on BL use in patients with reported allergies at an integrated health system. The BPA notified pharmacy staff that a patient with a documented BL allergy was receiving a NPA. Pharmacy staff assessed previous BL tolerance and clarified reaction, severity, and timing of the documented allergy. Patients were identified for analysis if they had a documented BL allergy within the electronic medical record and received at least one antibiotic during the study period. Results: A total of 418 patients were included in this analysis (180 preimplementation, 238 postimplementation). In the pharmacy‐driven assessment group, BL antibiotic use increased by 12.9% ( P = .008) in patients with a previously documented BL allergy with the largest use increase in 3rd/4th generation cephalosporins ( P = .045). Days of therapy for NPAs decreased in the postimplementation group, including aztreonam ( P = .006) and vancomycin ( P = .009). Conclusions: Our data suggests that a pharmacy‐driven allergy assessment using a BPA can increase appropriate use of BL antibiotics for hospitalized patients.